قصَّة الخلق بين الوهم والحقّ - السِّيسي, هاني (roa; Vol. 2 (2021): مجلة رؤى في الآداب والعلوم الإنسانية, 2021)
قصة الخلق بين الوهم والحق قصة خلق آدم عليه السلام أكثر القصص القرآني إثارة للدهشة .. وأشدها غموضاً .. لأنها تبحث في أصل حياة الإنسان في كوكب الأرض .. وارتباط الإنسان بهذه الأرض من أهم ما يفسر من الوجهة العلمية هذا التماهي الظاهري بين الجانب المادي في الإنسان / الجسد/ من جهة وأديم الأرض من جهة أخرى ... ونظراً لما لحق بهذه القصة من تصورات وتهاويم قد تنأى بها عن الحقيقة التي يمكن استنباطها من خلال الآيات القرآنية التي قدمت القصة في أكثر من موضع في سور مختلفة من القرآن .. وفي كل سورة يلقي السياق أضواء كاشفة على جوانب متعددة ومختلفة في قصة الخلق .. لذا رأينا أن نقدم قراءة جديدة لمشاهد القصة في مواضعها المتعددة في السياق القرآني .. وفي هذا الجزء الأول من البحث نكثف النظر لتأويل مشاهد هذه القصة في سورة البقرة   Abstract              With The Name Of God Sammary of Search about The Story of Creation between the fancy and The Truth The story of Adam's Creation is the most Quran stories amazing and obscurity ; because it searchs for origin of human' s life on the earth . The relation Of Man with this earth is the important thing that explains (from the scientific side ) the organic overlap between the human' s materialist side ( Man' s body ) and the dust of the earth . There are many imaginations about this story may be take it far away from the truth which we can extract from Quran's verses about this story in many places in different Suras of the Holy Quran . In every Sura we can find spot lights on many different sides about the story of creaturs . For this we saw that we must introduce new reading for scenes of the story in its places in Quran ; and in this part of the search we did our best efforts to explain these scenes in Baqara' s Sura